Hubungan antara Hardiness dan Regulasi Emosi Pada Perawat Rumah Sakit Usada Insani Kota Tangerang - GANITA GINANTI PUTRI; Ika Febrian Kristiana (Faculty of Psychology, Diponegoro University, 2017)
Emotional regulation is the ability to manage the emotions of the self, both positive and negative emotions. Hardiness is an ability that includes controls, challenges, and commitment to respond the pressures and negative effects of workload. This research aims to discover the correlation between hardiness and emotional regulation within nurses. The population in this research were 158 nurses from inpatient room of Usada Insani Hospital. Characteristics of subjects in this research are nurses with a minimum 1 year working period, female, and age between 20-40 years. This research uses simple random sampling technique which then obtained by 83 research subjects. Data collection was reached by Hardiness Scale with 32 items(α = 0,921) and 14 items of Emotion Regulation Scale (α = 0,801). Simple regression analysis showed a positive and significant relationship between hardiness and emotional regulation rxy = 0,533 (p <0.001). Hardiness contributes 28.4% to the varied trend of emotional regulation.